Overexpression of SIRT3 Suppresses Oxidative Stress-induced Neurotoxicity and Mitochondrial Dysfunction in Dopaminergic Neuronal Cells. - Lee, S.; Jeon, Y.M.; Jo, M.; Kim, H.J. (Experimental neurobiology, 2021)
Sirtuin 3 (SIRT3), a well-known mitochondrial deacetylase, is involved in mitochondrial function and metabolism under various stress conditions. In this study, we found that the expression of SIRT3 was markedly increased by oxidative stress in dopaminergic neuronal cells. In addition, SIRT3 overexpression enhanced mitochondrial activity in differentiated SH-SY5Y cells. We also showed that SIRT3 overexpression attenuated rotenoneor H2O2-induced toxicity in differentiated SH-SY5Y cells (human dopaminergic cell line). We further found that knockdown of SIRT3 enhanced rotenone- or H2O2-induced toxicity in differentiated SH-SY5Y cells. Moreover, overexpression of SIRT3 mitigated cell death caused by LPS/IFN-? stimulation in astrocytes. We also found that the rotenone treatment increases the level of SIRT3 in Drosophila brain. We observed that downregulation of sirt2 (Drosophila homologue of SIRT3) significantly accelerated the rotenone-induced toxicity in flies. Taken together, these findings suggest that the overexpression of SIRT3 mitigates oxidative stress-induced cell death and mitochondrial dysfunction in dopaminergic neurons and astrocytes.